Investigating the modulating effects of Afriplex GRT Extract on vascular function and antioxidant status in obese Wistar rat - Maqeda, Zimvo (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.